Notch Signaling Pathway Promotes Th17 Cell Differentiation and Participates in Thyroid Autoimmune Injury in Experimental Autoimmune Thyroiditis Mice - Hao Liu; Yiwen Li; Yujiao Zhu; Lei Ma; Haibo Xue (Mediators of Inflammation)
Purpose. To investigate whether the Notch signaling pathway participates in the occurrence and development of experimental autoimmune thyroiditis (EAT) by affecting the differentiation and function of Th17 cells. Materials and Methods. Experimental mice were randomly divided into a control group, an EAT-A group (porcine thyroid immunoglobulin- (pTg-) treated mice) and an EAT-B group (treated with the DAPT γ-secretase inhibitor before pTg). HE staining, IHC staining, flow cytometry, RT-qPCR, and ELISA were used to evaluate the degrees of thyroiditis, detect the percentage of Th17 cells and measure the expression of retinoic acid-related orphan receptor gamma t (RORγt), interleukin-17A (IL-17A), and the main components of the Notch signaling pathway. Results. The degrees of thyroiditis, the proportions of Th17 cells, and the expression of RORγt and IL-17A were significantly decreased in the EAT-B group after blocking the Notch signaling pathway by DAPT, and these parameters were significantly increased in the EAT-A group compared to the control group (all P<0.05). Additionally, the Th17 cell percentages and IL-17A concentrations in spleen mononuclear cells (SMCs) from EAT-A mice decreased in a dose-dependent manner after DAPT treatment in vitro (all P<0.01). Correlation analyses revealed that the Th17 cell percentages were positively correlated with the serum TgAb titers, Notch pathway-related mRNA expression levels, and IL-17A concentrations in EAT mice (all P<0.05). Conclusions. The expression of Notch signaling pathway components was upregulated in EAT mice, but blockade of the Notch signaling pathway alleviated the degree of thyroiditis, decreased the Th17 cell proportions, and downregulated the IL-17A effector cytokine both in vivo and in vitro. These findings suggested that the Notch signaling pathway may be involved in the pathogenesis of thyroid autoimmune injury in EAT mice by promoting the differentiation of Th17 cells.